2004
DOI: 10.5688/aj6803s7
|View full text |Cite
|
Sign up to set email alerts
|

Building a Process for Program Quality Enhancement in Pharmacy Education: Report of the 2003–04 Academic Affairs Committee

Abstract: According to the Bylaws of the AACP, the Academic Affairs Committee shall consider the intellectual, social, and personal aspects of pharmaceutical education. It is expected to identify practices, procedures, and guidelines that will aid faculties in developing studentsConsistent with a theme of exploring how AACP might foster organizational improvement and success among its institutional members, President Robert A. Kerr asked the 2003-04 AACP Academic Affairs Committee to suggest appropriate program assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…After reviewing its charges, the Committee decided to take the following approach to review a total of eight Academic Affairs Committee reports from 1999-2007 [1][2][3][4][5][6][7][8] which were focused on the following topics: Subsequently, the Committee met several times to discuss the findings and come to consensus on its relevance to the three identified priorities, developed a ranked list of these report recommendations inclusive of suggestions and policy statements, and identified recommendations that have not been implemented (e.g., those for which no evidence of action was found). In addition, the Committee provided recommendations regarding actions that can be taken by AACP regarding the reports' recommendations as well as their implementation status.…”
Section: Committee Processmentioning
confidence: 99%
“…After reviewing its charges, the Committee decided to take the following approach to review a total of eight Academic Affairs Committee reports from 1999-2007 [1][2][3][4][5][6][7][8] which were focused on the following topics: Subsequently, the Committee met several times to discuss the findings and come to consensus on its relevance to the three identified priorities, developed a ranked list of these report recommendations inclusive of suggestions and policy statements, and identified recommendations that have not been implemented (e.g., those for which no evidence of action was found). In addition, the Committee provided recommendations regarding actions that can be taken by AACP regarding the reports' recommendations as well as their implementation status.…”
Section: Committee Processmentioning
confidence: 99%
“…The report indicated that a useful assessment program incorporates results of institutional research to identify; "(1) evidence of effectiveness, and (2) indicators of needed change in a continuous quality improvement environment." 2 An increase has occurred in program-level assessment at US schools of pharmacy. A survey by Bouldin and Wilkin in 2000 found that only 29% of respondents had a formally adopted assessment plan in place.…”
Section: Introductionmentioning
confidence: 99%
“…17 In their report, the 2003-2004 AACP Academic Affairs Committee recommended that colleges and schools of pharmacy use the Astin model as a framework for organizing their data management. 18 Table 2 provides an example of UKCOP data sources sorted into this framework. The committee urges that use of the I-E-O model should depend on the purpose of the assessment questions that the college or school is asking.…”
Section: Assessing Impactmentioning
confidence: 99%